Terahertz refractive phenotype of living cells - Zhang, Guangxu; Wang, Yadi; Qian, Jiang; Wang, Yue; Li, Xueling; Lü, Junhong (Frontiers in Bioengineering and Biotechnology, 2023)
Cellular refractive index is a vital phenotypic parameter for understanding the cell functional activities. So far, there remains technical challenges to obtain refractive index of viable cells at the terahertz frequency in which contains rich information closely related to their physiological status. Here we introduce a label-free optical platform for interrogating cellular phenotypes to measure the refractive index of living cells in near-physiological environments by using terahertz spectroscopy with the combination of cellular encapsulation in a confined solution droplet. The key technical feature with cells encapsulated in aqueous droplets allows for keeping cellular viability while eliminating the strong adsorption of solvent water to terahertz signal. The obtained high signal-to-noise ratio enables to differentiate different cell types (eg. E. coli, stem cell and cancer cell) and their states under stress conditions. The integrating of terahertz spectroscopy to droplet microfluidic further realizes automated and high-through sample preparation and detection, providing a practical toolkit for potential application in cellular health evaluation and phenotypic drug discovery.